Implementasi Sistem Informasi Manajemen pada Lembaga Pendidikan atau Sosial Formal - Ahmad Fauzi Sarumpaet; Rayyan Firdaus (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Management Information Systems (MIS) have become a crucial component in enhancing operational efficiency and effectiveness in various educational institutions, including elementary, middle, and high schools. This article examines the implementation of MIS in schools, with a case study at SMP Negeri 11 Lhokseumawe. The implementation process, including planning, organizing, execution, and evaluation, is detailed comprehensively. The findings indicate that MIS can improve data management accuracy, expedite administrative processes, and increase parental involvement in the educational process. Despite facing challenges such as human resource readiness and infrastructure, proper support and systematic approaches enable schools to maximize the benefits of MIS. This article concludes that MIS is an effective tool in supporting school management and improving the quality of education.